Genetic and Phenotypic Characteristics of Congenital Hypothyroidism in a Chinese Cohort - Long, Wei; Guo, Fang; Yao, Ruen; Wang, Ying; Wang, Huaiyan; Yu, Bin; Xue, Peng (Frontiers in Endocrinology, 2021)
Background: The molecular etiology and genotype-phenotype correlation of congenital hypothyroidism (CH) remain unclear. Methods: We performed genetic analysis in 42 newborns with CH using whole-exome sequencing. Patients were divided into single gene group and multi-gene group according to the number of affected gene, or divided into monoallelic group, biallelic group and oligogenic group according to the pattern of detected variants. Clinical characteristics were compared between groups. Results: Thyroid dysgenesis (TD) was observed in 10 patients and goiter in 5 patients, whereas 27 patients had normal-sized gland-in-situ (GIS). We identified 58 variants in 5 genes in 29 patients. Genes with the most frequent variants were DUOX2 (70.7 %), followed by TSHR (12.1 %), DUOXA2 (10.3 %), and TPO (5.2 %). Variants in the genes causing dyshormonogenesis (DH) were more common than those in genes causing TD (87.9 % versus 12.1 %). Among the patients with detected variants, 26 (89.7%) patients harboring a single gene variant (single gene group), including 22 patients harboring biallelic variants (biallelic group) and 4 patients harboring monoallelic variant (monoallelic group). Three (10.3%) patients harbored variants in 2 or 3 genes (multi-gene group or oligogenic group). Compared with the single gene group, the L-T4 dose at 1 year of age was higher in the multi-gene group (P = 0.018). A controllable reduction in the L-T4 dose was observed in 25% of patients with monoallelic group and 59.1% of patients with the biallelic group; however, no patients were observed in the oligogenic group. Conclusions: Patients with normal-sized GIS accounted for the majority of our cohort. Genetic defects in genes causing DH were more common than those in genes causing TD, with biallelic variants in DUOX2 being dominant. DH might be the leading pathophysiology of CH in Chinese individuals.